3(y-6)=8414

Reduce the expression 8414 by cancelling the common factors.

Factor 14 out of 84.

3(y-6)=14⋅614

Factor 14 out of 14.

3(y-6)=14⋅614(1)

Cancel the common factor.

3(y-6)=14⋅614⋅1

Rewrite the expression.

3(y-6)=61

3(y-6)=61

Divide 6 by 1.

3(y-6)=6

3(y-6)=6

Divide each term in 3(y-6)=6 by 3.

3(y-6)3=63

Cancel the common factor of 3.

Cancel the common factor.

3(y-6)3=63

Divide y-6 by 1.

y-6=63

y-6=63

Divide 6 by 3.

y-6=2

y-6=2

Add 6 to both sides of the equation.

y=2+6

Add 2 and 6.

y=8

y=8

Solve for y 3(y-6)=84/14